2019
DOI: 10.3390/fermentation5020040
|View full text |Cite
|
Sign up to set email alerts
|

Dry Anaerobic Digestion of Food and Paper Industry Wastes at Different Solid Contents

Abstract: A large volume of food is being wasted every year, while the pulp and paper industry also generate a large amount of solid wastes on a daily basis, causing environmental challenges around the world. Dry anaerobic digestion (AD) of these solid wastes is a cost-effective method for proper management. However, dry digestion of these waste streams has been restricted due to their complex structure, the presence of possible inhibitors and inappropriate operating conditions. In light of this fact, dry digestion of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…60 days, of lag phase (Figure 2a). Jansson et al [43] also previously reported a long lag phase of 70 days for PW used in similar batch assays at S/I ratio (VS basis) of one with a TS of 16%. In an earlier report [44], the inhibitory effects of car-3-ene was examined on 14 different bacterial strains and the results showed antimicrobial effects with a minimum inhibitory concentration (MIC) of between 50-800 mg/L.…”
Section: Resultsmentioning
confidence: 84%
“…60 days, of lag phase (Figure 2a). Jansson et al [43] also previously reported a long lag phase of 70 days for PW used in similar batch assays at S/I ratio (VS basis) of one with a TS of 16%. In an earlier report [44], the inhibitory effects of car-3-ene was examined on 14 different bacterial strains and the results showed antimicrobial effects with a minimum inhibitory concentration (MIC) of between 50-800 mg/L.…”
Section: Resultsmentioning
confidence: 84%
“…Accordingly, the stable anaerobic process, and the promoted methane production that marked R2 and R3 compared to R1, were due not only to the adjusted C:N ratio, but also to the potential of CM and UBc to compensate for the deficit in terms of macro and micro-nutrients [12]. Therefore, the supply of certain nutrients ensured by the addition of both CM and UBc enhanced the buffering capacity by providing a suitable concentration of calcium (Ca), of around 0.61 g/kg TS and 0.57 g/kg TS, respectively [15], boosted the growth of all the methanogens by supplying 6.91 g/kg TS and 9.34 g/kg TS of Nickel (Ni) [54], and strengthened the process performance by adjusting the different rates of further required TEs [55]. Hence, FW anaerobic co-digestion with different types of organic residue generated from different sectors of activity seems to be a good alternative to simultaneously upgrading sustainable organic waste management, as well as a performant anaerobic digestion process under stable OLR.…”
Section: Effect Of Co-substrate Addition On Startup Conditions Of Fw-acodmentioning
confidence: 99%
“…Therefore, the supply of certain nutrients, ensured by CM addition, promotes the process performance as the exploited manure is characterized by a relatively high concentration of Calcium (Ca) of around 0.61 g/kg TS, which enhances the buffering capacity of AD (Arelli et al 2018). Furthermore, some macronutrients such as Potassium (K), Magnesium (Mg) and Phosphorus (P) as well as some TEs: Copper (Cu), Nickel (Ni), Cadmium (Cd) and Zinc (Zn), were identi ed in wide range for different substrates, particularly CM, which boost microorganisms' development (Jansson et al 2019). The same ndings were reported by Nordell et al (2016) revealing that manure is one of the most eminent substrates for biogas production as it stabilizes FW anaerobic processes by contributing the nutrients and TEs needed by the microbial community, particularly methanogens.…”
Section: Effect Of Mixing Substrates and C:n Ratio Regulation On Procmentioning
confidence: 99%